2019
DOI: 10.3233/jad-190332
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Phenocopy Syndrome of Behavioral Frontotemporal Dementia: Behavioral and Cognitive Fingerprint

Abstract: Behavioral and cognitive variables predicting behavioral frontotemporal dementia (bvFTD) versus primary psychiatric disorders mimicking bvFTD (phenocopy syndrome: bvFTD-PS) were studied. Forty-one probable/definite bvFTD and 16 bvFTD-PS patients were evaluated with cognitive battery, Neuropsychiatric Inventory, and Stereotypic and Ritualistic Behavior-revised questionnaires. Twenty-seven healthy subjects served as control. Severity of cognitive impairment/behavioral symptoms and profile of cognitive deficits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…12,16,23 Three studies concluded that MMSE scores differed significantly when phenocopies and bvFTDs were compared, 9,16,23 and 2 other studies found the opposite effect. 18,45 Phenocopies performed worse on the ACE than controls in 2 studies 16,19 and within the same range in another. 12 A difference was seen, also, when phenocopies and bvFTDs were compared.…”
Section: Cognitionmentioning
confidence: 72%
See 1 more Smart Citation
“…12,16,23 Three studies concluded that MMSE scores differed significantly when phenocopies and bvFTDs were compared, 9,16,23 and 2 other studies found the opposite effect. 18,45 Phenocopies performed worse on the ACE than controls in 2 studies 16,19 and within the same range in another. 12 A difference was seen, also, when phenocopies and bvFTDs were compared.…”
Section: Cognitionmentioning
confidence: 72%
“…However, a more recent study that included genetic tests in the diagnostic workup of participants noted that phenocopies were more likely than patients with probable or definite bvFTD to score for depression on the Neuropsychiatric Inventory. 45 Gossink et al noted that progression among a group of genetically screened patients with a late-onset frontal lobe syndrome was predicted by a positive personal or family history of psychiatric disorders. 46 These studies add to the complexity of the phenocopy formulation and underline the need for combined psychiatric, psychological, and neurological expertise in their assessment.…”
Section: Etiological Possibilitiesmentioning
confidence: 99%
“…The main focus of pharmacological research over the past 50 years has been the identification of cognitive enhancers; however, no US Food and Drug Administration (FDA)-approved drugs for AD have been reported for the past two decades [7]. Behavioral disorders (BDs) (psychotic, depressive, anxiety, sleep disorders, and inappropriate sexual behaviors) are common (10- There is not a prototypical pattern of BDs in different dementia types; however, BDs tend to be more prevalent in FTD, in cases where the compromise of frontotemporal regions is more relevant [18][19][20], and in cases with mild traumatic brain injury (TBI) [21] where DNA damage-induced cellular senescence pathways have been identified [22]. Apathy, depression, dysphoria, agitation, aggression, hallucinations, and delusions are frequent distressing symptoms in dementia [14].…”
Section: Introductionmentioning
confidence: 99%
“…From the current literature, it appears that there may be an association between phFTD and other psychiatric disorders such as bipolar disorder, depression, and cluster C personality disorders [ 10 ]. Both Hornberger et al and Bussè et al found a correlation between depression and phFTD and suggested that it may assist in distinguishing between bvFTD and phFTD [ 11 , 12 ]. Our patient adds another example to the literature of an individual with suspected phFTD and a previous diagnosis of major depression.…”
Section: Discussionmentioning
confidence: 99%
“…This patient had been experiencing depression since 1983. Other authors have expressed that patients with depressive symptoms often cloud providers' decision-making in diagnosing phFTD due to wanting to address this issue first as the primary diagnosis [ 10 , 12 ]. Future studies should consider the concurrence of other behavioral disorders such as depression as a feature in identifying phFTD.…”
Section: Discussionmentioning
confidence: 99%